Information Content of the Voluntary Disclosure on Stock Returns: Evidence from Listed Commercial Banks in Thailand - Gunarapong, Nathaporn; Tongkong, Supa; Boonyanet, Wachira (Rajapark Journal, 2022)
The objective of this study was to investigate the information value of voluntary disclosure over stock returns. The study developed a self-constructed and unweighted voluntary disclosure index to the literature. The index comprised 185 information items and was used to measure the level of voluntary disclosure of listed commercial banks in Thailand over the 2016-2019 reporting period. Data collection was based on annual reports, the SET Market Analysis and Reporting Tool and other sources that were from the most recent year for which data were available at the time. The research data were analyzed using content analysis and descriptive and multiple regression analyses including pooled, fixed effects and random effects. The findings indicated the voluntary disclosures were significant and had a positive effect on stock returns while non-performing loans demonstrated a positive effect to the total voluntary disclosures which simultaneously affected on stock returns in a positive manner. Conversely, capital reserve to total risk-weighted assets, net profit to total number of employees, net profit to total equity, and liquid assets to total deposits had no significant impact on stock returns. The study is beneficial to both bank managers and investors seeking to improve their wealth from using voluntary disclosure information.